Decision-Making in the Surgical Treatment of Breast Cancer: Factors Influencing Women’s Choices for Mastectomy and Breast Conserving Surgery - Bellavance, Emily Catherine; Kesmodel, Susan Beth (Frontiers in Oncology, 2016)
One of the most difficult decisions a woman can be faced with when choosing breast cancer treatment is whether or not to undergo breast conserving surgery (BCS) or mastectomy. The factors that influence these treatment decisions are complex and involve issues regarding access to healthcare, concerns for cancer recurrence, and the impact of surgery on body image and sexuality. Understanding these factors will help practitioners to improve patient education and to better guide patients through this decision-making process. While significant scientific and societal advances have been made in improving women’s choices for the breast cancer treatment, there are still deficits in the decision making processes surrounding the surgical treatment of breast cancer. Further research is needed to define optimal patient education and shared decision-making practices in this area.